Effects of titanium dioxide nanoparticles on human keratinocytes. (2nd January 2017) - Wright, Clayton; Iyer, Anand Krishnan V.; Wang, Liying; Wu, Nianqiang; Yakisich, Juan S.; Rojanasakul, Yon; Azad, Neelam
Abstract: Titanium dioxide (TiO2 ) is a ubiquitous whitening compound widely used in topical products such as sunscreens, lotions and facial creams. The damaging health effects of TiO2 inhalation has been widely studied in rats, mice and humans showing oxidative stress increase, DNA damage, cell death and inflammatory gene upregulation in lung and throat cells; however, the effects on skin cells from long-term topical use of various products remain largely unknown. In this study, we assessed the effect of specific TiO2 nanoparticles (H2 TiO7 ) on a human keratinocyte cell line (HaCaT). We performed a comparative analysis using three TiO2 particles varying in size (Fine, Ultrafine and H2 TiO7 ) and analyzed their effects on HaCaTs. There is a clear dose-dependent increase in superoxide production, caspase 8 and 9 activity, and apoptosis in HaCaTs after treatment with all three forms of TiO2 ; however, there is no consistent effect on cell viability and proliferation with either of these TiO2 particles. While there is data suggesting UV exposure can enhance the carcinogenic effects of TiO2, we did not observe any significant effect of UV-C exposure combined with TiO2 treatment on HaCaTs. Furthermore, TiO2 -treated cells showed minimal effects on VEGF upregulation and Wnt signaling pathway thereby showing no potential effect on angiogenesis and malignant transformation. Overall, we report here an increase in apoptosis, which may be caspase 8/Fas-dependent, and that the H2 TiO7 nanoparticles, despite their smaller particle size, had no significant enhanced effect on HaCaT cells as compared to Fine and Ultrafine forms of TiO2 .